2021
DOI: 10.3389/fpsyg.2021.664453
|View full text |Cite
|
Sign up to set email alerts
|

A Career Crafting Training Program: Results of an Intervention Study

Abstract: This intervention study examined the effects of a career crafting training on physicians' perceptions of their job crafting behaviors, career self-management, and employability. A total of 154 physicians working in two hospitals in a large Dutch city were randomly assigned to a waitlist control group or an intervention group. Physicians in the intervention group received an accredited training on career crafting, including a mix of theory, self-reflection, and exercises. Participants developed four career craf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…If so, training them how to do so might enhance their job crafting behavior, as was found in previous intervention studies. 16,30 In turn, this could positively affect their well-being, in line with previous job crafting intervention studies. 16,31 Future research could further explore if job crafting is an effective strategy to better deal with a highly demanding work environment by training physicians in how to engage in job crafting behaviors.…”
Section: T a B L Esupporting
confidence: 80%
“…If so, training them how to do so might enhance their job crafting behavior, as was found in previous intervention studies. 16,30 In turn, this could positively affect their well-being, in line with previous job crafting intervention studies. 16,31 Future research could further explore if job crafting is an effective strategy to better deal with a highly demanding work environment by training physicians in how to engage in job crafting behaviors.…”
Section: T a B L Esupporting
confidence: 80%
“…p1: difference between pre and post / p2: difference between pre and post 3 months / p3: difference between post and post 3 months/ *statistically significant at p <0.05/ ** highly statistically significant at p <0.01 apply job crafting to improve their work outcomes (17) . On the same line with this result, Van Leeuwen et al (2021) (18) found that applying (2019) (19) showed in his study that the impact of the application of a program about job crafting create a positive impact on all dimensions job crafting. Also, the program developed by Dubbelt et al (2016) (20) found that studied sample utilize their personal and past experiences about job crafting which who worked on improving specially their clinical outcomes as work involvement and job commitment.…”
Section: Phases Of Training Program (N=65)mentioning
confidence: 64%
“…Other researchers have focused on examples of job crafting throughout someone's careeracross jobs and rolesas well as family, organizational and environmental influences on these careers (Vidwans and Du Plessis, 2019;Vidwans and Whiting, 2021). A recent intervention study operationalized career crafting as job crafting, which reflects the short-term career, and career self-management, which addresses the long-term or series of jobs that form the career (Van Leeuwen et al, 2021). The authors…”
Section: Home Craftingmentioning
confidence: 99%